Changes in Colonial Labor Policy Post-Chinese Workers' Uprising in Wanayasa 1832 - Misbah, Misbahudin (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This article explores the transformation of colonial labor policy in the Dutch East Indies following the rebellion of Chinese workers at the Wanayasa tea plantation in 1832. Triggered by exploitative labor practices, including irregular wages, forced labor, and the absence of formal contracts, the uprising marked a turning point in labor governance under colonial rule. The research employs a historical-sociological method, supported by Ted Robert Gurr’s theory of Relative Deprivation, to examine the structural inequalities that led to collective resistance. Primary sources include colonial archives, local manuscripts, and autobiographical reports from colonial officials. The study finds that the rebellion pressured the colonial government to issue the Governor-General’s Decree of 1833, introducing formal labor contracts and a more structured wage system. While implementation remained inconsistent, this marked the beginning of a shift from informal exploitation to regulated labor relations. The article contributes a novel perspective by combining historical narrative with social theory to highlight the agency of marginalized labor groups in shaping colonial policy. It also offers new insights into the roots of labor consciousness and early worker mobilization in Indonesia’s colonial context.